2020
DOI: 10.1177/0886260519900323
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Minor Sex Trafficking: A Case Series of Male Pediatric Patients

Abstract: Domestic minor sex trafficking (DMST) is the commercial sexual exploitation of children (<18 years old) who are U.S. citizens or lawful permanent residents, victimized within U.S. borders. There is limited knowledge and research in regard to male involvement in DMST outside the context of homelessness and runaway youth. To our knowledge, no research specifically examines at-risk or involved male youth from a larger dataset of youth who present to a child abuse outpatient medical clinic. The objective of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
(33 reference statements)
2
8
0
Order By: Relevance
“…To our knowledge, this is the first study to examine a broad set of adolescent and adult health associations with childhood and adolescent CSE exposure using nationally representative data. We found that CSE exposure before or during adolescence was common—1 in 25 young people reported experiencing CSE during adolescence—confirming findings from previous Add Health studies, 1,23 and the prevalence and frequency of adolescent CSE exposure was higher among males than among females. Males face many barriers to identification and access to health care and social services in the community, 3 some of which may have been overcome by the confidential format of the Add Health survey.…”
Section: Discussionsupporting
confidence: 89%
“…To our knowledge, this is the first study to examine a broad set of adolescent and adult health associations with childhood and adolescent CSE exposure using nationally representative data. We found that CSE exposure before or during adolescence was common—1 in 25 young people reported experiencing CSE during adolescence—confirming findings from previous Add Health studies, 1,23 and the prevalence and frequency of adolescent CSE exposure was higher among males than among females. Males face many barriers to identification and access to health care and social services in the community, 3 some of which may have been overcome by the confidential format of the Add Health survey.…”
Section: Discussionsupporting
confidence: 89%
“…Experts focused on the counselor’s ability to assess for risk factors and indicators correlated with a higher incidence of CST. These findings support literature on CST assessment (Clawson et al, 2009; Hardy et al, 2013; Moore et al, 2020; O’Brien et al, 2017; Romero et al, 2021). Experts agreed that the counselor holds the onus of assessment, considering that youth seldom self-identify, and recommended educational and training experiences to effectively assess for CST with any child.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, certain circumstances increase risk. These factors include individual substance use (Cole et al, 2016), family substance use, running away (Clawson et al, 2009), family conflict or abandonment, lower socioeconomic status (Hardy et al, 2013), physical abuse and/or sexual abuse (Cole et al, 2016), homelessness, and involvement with foster care and juvenile systems (Moore et al, 2020).…”
Section: Child Sex Traffickingmentioning
confidence: 99%
“…Females were found to be significantly protected against DMST, compared to males, in the multivariable regression results. Given that males are often overlooked or excluded from analyses focused on DMST experiences, these Add Health results are valuable in demonstrating the connections between DMST and community violence for both males and females, as the connection between DMST and community violence were not significantly distinct by biological sex ( Moore et al, 2020 ; Robert & Willis, 2013 ). The protective relationship detected here for females may be due to the way in which the DMST measure was asked in Add Health.…”
Section: Discussionmentioning
confidence: 99%